Clinical outcomes in patients hospitalized due to heart failure with Chagas disease vs other etiologies in the USA - Echeverría, Luis Eduardo; Rojas, Lyda Z; Duque, Carolina; Marcus, Rachel; Contreras, Johana; Gómez Ochoa, Sergio Alejandro (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2025)
Chagas disease (CD) affects approximately 300 000 individuals in the USA. However, its impact on heart failure (HF) hospitalizations in the USA as non-endemic setting remains poorly characterized. We aimed to assess the clinical profile and acute clinical outcomes of HF hospitalizations in patients with CD compared with those without CD in the USA.The National Inpatient Sample (2002-2021) was queried for adult hospitalizations with a primary diagnosis of HF. Multivariable regression models assessed the association between CD diagnosis and in-hospital mortality, length of stay and total healthcare costs.Among 2 990 959 HF hospitalizations, 154 (0.005%) had a CD diagnosis. After adjustment, CD was associated with longer length of stay (β=5.94 d, 95% CI 4.92 to 6.97) and higher total healthcare costs (β=US$94 886, 95% CI 79 282 to 110 490), but not differential mortality (OR=0.63, 95% CI 0.19 to 2.11). Sex-stratified analyses revealed longer hospitalizations in females (β=8.58 vs 3.75 d), but higher healthcare costs in males (β=US$106 667 vs 80 089) with CD compared with their non-CD counterparts.In the USA, HF hospitalizations with CD are characterized by increased healthcare utilization, despite similar mortality compared with non-CD admissions. Sex-specific differences in outcomes highlight the need for targeted approaches to care delivery. Larger studies focused on CD cases detection are needed to have a better understanding of the burden of this neglected disease in non-endemic settings.
Gesehen am 05.02.2025